Effect of Providing Compost and NPK Fertilizer 16:16:16 on the Growth and Production of Cucumber Plants (Cucumis sativus) - Saragih, Meylin Kristina; Sihombing, Parsaoran; Sitorus, Efbertias; Panataria, Lince Romauli (PT. Riset Press International, 2024)
The research aims to determine the Effect of Providing Compost and NPK fertilizer 16:16:16 on the Growth and Production of Cucumber Plants (Cucumiss sativus). This research used a factorial Randomized Group Design (RAK) using 2 treatment factors. The first factor is dose treatment, which consists of 3 levels, namely K1: No compost, K2: Compost dose 10 t/ha or 1 kg/plot, and K3: Compost dose 20 t/ha or 2 kg/plot. The second factor is the dose of NPK 16:16:16 fertilizer, namely:N1: NPK fertilizer dose 250 kg/ha or equivalent to 25g/plot, N2: NPK fertilizer dose 350 kg/ha or equivalent to 35g/plot, N3: NPK fertilizer dose 450 kg/ha or equivalent to 45g/plot. The results showed that the dose of compost had a significant effect on fruit weight; a dose of 2kg/lot of chicken coop compost produced the heaviest fruit weight but had no significant effect on plant height, number of leaves, flowering time, fruit length, fruit diameter and number of fruit on cucumber plants. The dose of NPK 16:16:16 fertilizer had no significant effect on all observed parameters. The interaction between the chicken coop compost dose and the NPK 16:16:16 fertilizer had no significant effect on all observed parameters.